Services Requested and Received by Consumers with Chemical Sensitivities at the Centers for Independent Living - Gibson, Pamela Reed; Suwal, Sahisna; Sledd, Lauren G. (Disability Studies Quarterly, 2009)
<!--[if gte mso 9]> Normal 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]-->This paper presents results from surveys of 41 persons with environmental sensitivities (ES) who requested help from Centers for Independent Living (CIL), primarily in the U.S. The most common requests were for help with safe housing, employment services, and application for SSDI. Consumers with ES encountered multiple problems not only with receiving services, but also simply with "getting in the door," as many centers were not equipped to understand or serve persons with chemical or electromagnetic sensitivities. We present suggestions from respondents for improved access and service for this population and for training of CIL advocates.